2012
DOI: 10.2174/1874325001206010276
|View full text |Cite
|
Sign up to set email alerts
|

Treating Stiffness After Total Knee Arthroplasty: A Technical Note and Preliminary Results

Abstract: Total Knee Replacement is used to treat pain, stiffness and reduced range of movement. It has been estimated that a minimum of 90 degrees of range of motion in the knee is required for normal activities of daily living. In this article we demonstrate a technical note with a small patient series about the methods of treating knee stiffness after Total Knee Replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(21 reference statements)
0
5
0
1
Order By: Relevance
“…One of the benefits of delaying TKR in older individuals may be to avoid risks associated with the surgery or with subsequent required revisions. The complications associated with TKR have been extensively studied and include infection, 15,16 pulmonary embolism, 17,18 thromboses, 19,20 fat embolism, 21,22 hemarthrosis, 23,24 patellar fracture, 16,25 heterotopic ossification, 26,27 stiffness, 16,28 nerve damage, 29,30 vascular injuries, 16,31 urinary complications, 32,33 and increased mortality. 34,35 A recent study showed that postoperative mortality more than tripled in patients !…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the benefits of delaying TKR in older individuals may be to avoid risks associated with the surgery or with subsequent required revisions. The complications associated with TKR have been extensively studied and include infection, 15,16 pulmonary embolism, 17,18 thromboses, 19,20 fat embolism, 21,22 hemarthrosis, 23,24 patellar fracture, 16,25 heterotopic ossification, 26,27 stiffness, 16,28 nerve damage, 29,30 vascular injuries, 16,31 urinary complications, 32,33 and increased mortality. 34,35 A recent study showed that postoperative mortality more than tripled in patients !…”
Section: Discussionmentioning
confidence: 99%
“…14 TKR is also costly and may require future revisions. In addition, TKR has been associated with various complications, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] including an increased risk of mortality. 34,35 Because of ongoing pain, many patients (range, 20-40%) remain dissatisfied following a TKR.…”
mentioning
confidence: 99%
“…However, it represents an abundance of scar tissue or fibrosis occurring either idiopathically or secondary to a patient’s predisposition to it. 1618 The implication is that arthrofibrosis is a patient risk factor, although as it is only present following surgery and may be considered a postoperative factor.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Kuadriseps snip ya da V-Y plasti yöntemiyle, kuadriseps tendonunun bütünlüğüne zarar vermeksizin kontrollü gevşetme yapılabilir. [20] Genellikle, bu yaklaşımla hastanın ameliyat sonrası rehabilitasyon protokolünü modifiye etmek gerekmez. İleri derecede ankiloze dizlerde ise son çare olarak tuberositas tibia osteotomisi denenebilir.…”
Section: Açık Gevşetme Ve Sınırlı Revizyon Artroplastisiunclassified